Flow investigation of multiphase manganese slags - V Rimal; d M. Tangstad (The Australasian Institute of Mining and Metallurgy, 2024)
Multiphase slags form the basis of the reduction pathway for manganese ferroalloy production. The present work aims to understand the flow of slag through the coke bed based on experimentation in controlled conditions. Synthetic slags of different basicities were evaluated for their phase composition, viscosity, and flow. The two-phase slag will have two zones: a liquid slag zone and a multiphase zone. The multiphase zone will consist mostly of a solid phase with some liquid slag between the solid particles. The multiphase part will hence have a high viscosity. The liquid zone will flow into the coke bed while the multiphase area will stay. With increasing reduction, the multiphase area will decrease in size until the solid phase is gone and the whole slag will flow into the coke bed. The effective viscosity of slag will decrease with the lowering of the solid oxide phase. The results from flow experiments confirmed that the segregation of phases occurs when slag flows through the coke bed. It is observed that the flow is dependent both on the size of the void and the viscosity of slag.